223k views
3 votes
Pls help thank you so much

Pls help thank you so much-example-1
User Mcliedtk
by
5.6k points

2 Answers

6 votes
Here’s my working out. Hope this helps :)
Pls help thank you so much-example-1
User Lassej
by
6.3k points
5 votes

Answer:


g=(x-2)/(3)

Explanation:


x=3g+2

- Reverse it to take "
g" on the left side


3g+2=x

- Take
+2 on the other side which will be
-2


3g=x-2

- Take "
3" on the other side

{remember:
3 is being multiplied by
g, so when you carry it on the other side it will be divided by the rest}

therefore:-
g=(x-2)/(3)

Hope it helps.....

User Paulo Coghi
by
6.5k points